Pengaruh Model Pembelajaran Assure Dalam Pendidikan Agama Islam Terhadap Minat Belajar Siswa SMPN 1 Bekasi - Assyifa Amalia; Farah Fauziah; Rijal Fadhilah; Purnama Putra (Program Studi Pendidikan Agama Islam, Sekolah Pascasarjana Universitas Islam 45, 2023)
The role of the teacher is very important in the world of education, because the teacher is in charge and responsible for motivating, facilitating, educating and training students. One way to overcome the difficulties experienced by students is to increase students interest in learning in students who students experience difficulties. Teachers teach with methods that make students active in carrying out learning so that students are happy and active in answering teacher questions. This study aims to find out how the teacher's role in increasing students interest in learning. Teachers teach with methods that make students active in carrying out learning so that students are happy and active in answering teacher questions. The method used by researchers is a quantitative research method with quasi-experimental techniques. is one of the determinants in improving human resources. The learning design developed by the teacher is designed by implementing the ASSURE model in implementing the learning process. The ASSURE model is a learning model designed to strengthen effective and efficient learning, especially in learning activities that use media and technology. Where this integrated thematic learning is learning that links several fields of study into an interrelated theme to provide real experiences for students so that they can develop student knowledge an improve learning outcomes for students. In addition, it also helps teachers in evaluating the learning process that has been implemented.